O PROEJA vai fazer falta: uma análise de diferentes projetos educativos a partir dos discursos de estudantes nas aulas de Matemática - Paula Reis de Miranda (2015)
This work aims to identify and analyze ways in which the subjects of the Technical Course in Community Health Agent in the mode PROEJA of the IF Sudeste MG - Campus Rio Pomba conceive the PROEJA and its place in this experience. In particular, we sought to understand how the students of this course take apropriation of the various educational projects that are configured on it (the ones proposed by the Base Document of PROEJA, the Pedagogical Project of the Course, and the Analytical Programs of disciplines; the ones forged by the classes dynamics and by the students expectations and individual desires), focusing on the teaching of Mathematics and its contribution to an integrated learning experience from Basic Education to Vocational Training. To achieve this goal, this research drew on the classroom ethnography and discourse analysis to catch, in the discursive interactions that take place in classes of mathematics and vocational training, utterances in which the subjects conceive and denounce tensions between curricular perspectives that establish and are settled in educational activities in which they participate. Based on a post-critical approach, we understand the reflections that related curriculum, mathematics, human education and vocational training, reflections which where enabled by classroom situations, as discursive practices, and as these discursive practices have their reference in the experience of learning and using math, we have considered them as numeracy practices here. From this approach we could identify, in those utterances, echoes of technicist discourse that emerged in the second half of the last century and which relate the forming of a curricular project to the knowledge we have of the life of the student, the role played by the expert and the conditions of apprentices (EJA and PROEJA) in the constitution of the curriculum. In an educational and political landscape in that "mythical values of the past or modern economic imperatives" confront proposals for emancipatory integrated training, this work seeks to contribute to a broader discussion of the PROEJA, on the Education of Youth and Adult, on Vocational Education and on mathematics education, as the work focuses and makes available to education professionals - teachers, researchers, developers, implementers and policy evaluators - an analysis of the difficulties and successes, the demands and contradictions, fears and expectations, which shape the educational processes that happen in PROEJA, from the positions taken by male and female students of this Program in classroom interactions.